2023
DOI: 10.1108/ijebr-07-2023-0684
|View full text |Cite
|
Sign up to set email alerts
|

Effectuation and strategic evolution for sustainable longevity: the case of a 19th-generation family firm

Dianne H.B. Welsh,
Orlando Llanos-Contreras,
Melany Rebeca Hebles

Abstract: PurposeThis article explains the causal mechanism supporting sustainable longevity by analysing the last three generations of one of the oldest family firms in Latin America.Design/methodology/approachAn explanatory single-case qualitative research based on critical realism explores why and how this family firm has been able to maintain its multigenerational longevity.FindingsLos Lingues's evolutionary strategy, driven by transgenerational entrepreneurship under effectuation, has supported this family firm's s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Other studies have shown strategies and mechanisms developed by family firms to navigate financial distress and minimal financial rewards ( Glover and Reay, 2015 ). More recently, research has informed on the mechanisms, strategic logic, and motivations behind a family firm’s strategic evolution to support sustainable longevity ( Welsh et al, 2023 ). Our study suggests that job satisfaction is critical for these firms’ resilience and continuity.…”
Section: Contributions To Theory and Practicementioning
confidence: 99%
“…Other studies have shown strategies and mechanisms developed by family firms to navigate financial distress and minimal financial rewards ( Glover and Reay, 2015 ). More recently, research has informed on the mechanisms, strategic logic, and motivations behind a family firm’s strategic evolution to support sustainable longevity ( Welsh et al, 2023 ). Our study suggests that job satisfaction is critical for these firms’ resilience and continuity.…”
Section: Contributions To Theory and Practicementioning
confidence: 99%